Forms and Content of Social Advertising: Raising Risk Awareness and Alert Behavior Patterns in Online Communication - Aleksandr V. Ovrutsky; Gulnora K. Ovrutskaya (Виртуальная коммуникация и социальные сети)
As teenagers and young people grow more and more dependent on online communication, they become more psychologically vulnerable to numerous potential threats that thrive on the Internet. Social advertising may help to develop the necessary risk awareness and alert behavior patterns. The article describes six Safe Internet Advertising Campaigns that popularize risk awareness in online communication. The authors conducted a comparative analysis of the verbal and visual elements to identify the target audiences. The review covered publications connected with online communication risks, safe behavior, and social advertising campaigns. In terms of structure, the advertising messages included verbal and visual components with a dominant visual element. The title set consisted of a slogan and a headline, with no advertising text. Unsafe contact prevention proved to be the main topic while parents were the main target audience. The metaphor appeared to be the most popular visual stylistic device. The ads appealed to the emotions and motivation of the target audience, i.e., fear, anxiety, failure avoidance, etc. The authors also classified the advertisers, advertising statistics, RAM conductors, and strategies, as well as assessed the potential effectiveness of social advertising campaigns. The article is a summary of experience in using social advertising for developing risk awareness and alert behavior in online environment. It proves that social advertising could be an effective tool in preventing negative consequences of online communication.